2015
DOI: 10.16984/saufenbilder.77095
|View full text |Cite
|
Sign up to set email alerts
|

Stereo kamera sisteminde aykırılık haritaları yardımıyla nesne uzaklıklarının tespit edilmesi

Abstract: ÖZBu çalışmada stereo kamera sistemi ile farklı cisimlerin derinliklerinin yani paralel kamera düzlemine uzaklıklarının tespit edilmesi amaçlanmıştır. Kurulan test düzeneğinde sağ ve sol görüntünün elde edilmesi için iki adet sabitlenmiş kamera ve bunlardan alınan görüntüleri işleyen bir adet bilgisayar bulunmaktadır. Kameralar sabit olarak yerleştirildikten sonra satranç tahtası yardımıyla kalibre edilmiştir. Kalibre işleminden sonra her iki kamera için esas ve temel matrisler, birinci ve ikinci kameralar ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Collecting of two image pattern It Show the inner components of a standard stereo vision system. It observed that the axes and image planes are composed of a parallel system when a stereo-camera whose camera planes are properly aligned and lens disturbances are completely measured and analysed [14]. The estimation of the height of tress and vegetation near the base poles to the depth map is inversely proportional to the disparity map [15].…”
Section: Methods Of Machine Visionmentioning
confidence: 99%
“…Collecting of two image pattern It Show the inner components of a standard stereo vision system. It observed that the axes and image planes are composed of a parallel system when a stereo-camera whose camera planes are properly aligned and lens disturbances are completely measured and analysed [14]. The estimation of the height of tress and vegetation near the base poles to the depth map is inversely proportional to the disparity map [15].…”
Section: Methods Of Machine Visionmentioning
confidence: 99%